2014
DOI: 10.1063/1.4901910
|View full text |Cite
|
Sign up to set email alerts
|

The local surface plasmon resonance property and refractive index sensitivity of metal elliptical nano-ring arrays

Abstract: In this paper, we systematically investigate the optical property and refractive index sensitivity (RIS) of metal elliptical nano-ring (MENR) arranged in rectangle lattice by finite-difference time-domain method. Eight kinds of considered MENRs are divided into three classes, namely fixed at the same outer size, at the same inner size, and at the same middle size. All MENR arrays show a bonding mode local surface plasmon resonance (LSPR) peak in the near-infrared region under longitudinal and transverse polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…By using the finite-difference time-domain method, Lin et al investigated the LSPR properties and refractive index sensitivity of Ag elliptical nano-ring arranged in rectangle lattice [2]. They found that high sensitivity can be achieved by small particle distance arrays composed of metal elliptical nano-rings with big inner size and small ring-width.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the finite-difference time-domain method, Lin et al investigated the LSPR properties and refractive index sensitivity of Ag elliptical nano-ring arranged in rectangle lattice [2]. They found that high sensitivity can be achieved by small particle distance arrays composed of metal elliptical nano-rings with big inner size and small ring-width.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the tunable plasmonic spectrum properties of metal nanoparticles have attracted extensive investigations and displayed well potential applications in analytical chemistry to biology [1][2][3][4]. The intense light absorption from localized surface plasmon resonance (LSPR) is very sensitive to the tiny change of the environmental dielectric constant, thus the metal nanostructurebased spectroscopic analysis could be used in the detection of the concentration induced ultra small refractive index changes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As a silver based sensor, metal elliptical nanoring (MENR) arrays performance is investigated [6]. The MENR consists of silver nanorings arranged in rectangle lattice based on SiO 2 substrate.…”
Section: Introductionmentioning
confidence: 99%